Synthesis and perspectives on the study of ant‐plant interaction networks: A global overview - Juárez‐Juárez, Brenda; Dáttilo, Wesley; Moreno, Claudia E. (Ecological entomology, 2023)
In recent decades, the interest in complexity of ant‐plant relationships has increased considerably. However, because the spatial and biological information generated on ant‐plant interaction networks is dispersed in the literature it is necessary to synthesise current information, detect knowledge gaps, and outline needs for research leading to the development of a broad and systematic view on the subject. Here, we present a global synthesis of the scientific articles dealing with ant‐plant interaction networks, through a quantitative scientometric analysis to establish the state of the art in this topic and to propose future perspectives. We gather 54 articles published between 2006 and 2020 in 32 different scientific journals, which were written by 132 different authors. The studies were conducted in 15 countries and 9 biomes (most of them (61%) were in tropical lowlands), but Brazil and Mexico represented 87% of the global scientific production. Although most studies are related to ant‐plant interactions involving extrafloral nectaries (72%) usually in diurnal samplings, we also found other types of ant‐plant relationships such as floral nectar, extrafloral nectar, sap, myrmecophyte, seed/fruit, foraging substrate, and nesting sites. Furthermore, most studies used a bipartite framework of ant‐plant interaction mediated by only one type of resource, and researchers often reported a nested pattern of species interactions. Finally, we identify some regions, biotic interactions involving different types of resources, spatio‐temporal scales, and research questions that need further research for a better understanding of the complexity ant‐plant networks. A quantitative scientometric analysis revealed a notable increase in studies of ant‐plant interactions using graph theory, but they are geographically biased towards lowland biomes of Mexico and Brazil. Some information gaps are due to the lack of standardised sampling methods and network descriptors, and the focus on bipartite frameworks of interactions involving extrafloral nectaries. We detect challenging topics that are beginning to be addressed, such as the scale of effect, macroecological patterns, and the impacts of human‐modified environments on ant‐plant networks.